Perceptions of Technological Change at Work through a Gender Lens - Katrin Golsch; Marco Seegers (Gender a Výzkum)
In Germany, like in many other countries, much of the research on technological changes and their consequences has been devoted to investigating the field of industrial production. A shortcoming of this research is that many female-dominated occupations are excluded per se from consideration. However, whether and to what extent men's and women's perceptions of technological changes in their workplace differ is an important subject of debate. This article addresses the following questions: To what extent are men and women experiencing changes in the technologies of their workplace? Are women less likely to experience such changes? Do men and women anticipate to differing degrees a threat to their future job security and the skills demanded of them? And do they expect technological changes in their workplace to impact their health or work performance demands? The analysis, based on data from the Socio-Economic Panel Study (SOEP, 2015-2017), compares men and women across gender-typical and gender-atypical occupations and identifies conditions that increase or decrease perceived risks of technological change at work. The results indicate that technological change is perceived as most threatening in female-dominated occupations, and especially by women.